The Impact of the Covid-19 Pandemic on Vietnam’s Exports - Anh, Tran Kim; Trang, Le Mai; Tuan, Hoang Anh; Hien, Nguyen Thi; Ha, Dinh Thi (International Journal of Membrane Science and Technology, 2023)
The COVID-19 pandemic outbreak expanded worldwide, disrupting trade on a scale never before seen, as well as that of individual nations, notably Vietnam. The complicated developments of the COVID-19 pandemic have significantly affected Vietnam’s economic growth in general and export activities in particular. Since joining the WTO, Vietnam’s exports have grown tremendously and become an essential driver of economic growth. However, due to the high openness of the economy, Vietnam’s exports are highly dependent on impacts from external shocks with global influence, especially the Covid-19 pandemic. The following research paper uses a mixed regression model to analyze and assess the impact of the Covid-19 pandemic on Vietnam’s export activities through such contents as export turnover, export product, export market, and exporters.